The Effect of Education on Self Efficacy and Anxiety levels Before Childbirth During the Covid-19 Pandemic in Third Trimester Pregnant - Anggraini, Fritria Dwi; Handayani, Nanik (STRADA : Jurnal Ilmiah Kesehatan, 2021)
Childbirth without direct assistance by the family and the condition of the clinic that is not conducive due to this pandemic will risk making the mother even more anxious and insecure, especially if the mother does not fully understand the current condition. Lack of understanding will make mothers feel anxious. This study used a quasi-experimental study with a pre-test-post-test group. The population is 48 respondents. The independent variable is education about Covid and dependent variable is Self-efficacy and the level of maternal anxiety. Data collection using a questionnaire, anxiety with DASS 42 and self-efficacy will be measured using the general self-efficacy scale (GSES). Data analysis used Pair T test with α = 0.05. The results of the paired T-test statistical test obtained pre post test analysis of education, the self-efficacy variable stated the value of ρ = 0.02 and the variable degree of anxiety the value of ρ = 0.01.